Weighted and Maximally Hypoelliptic Estimates for the Fokker-Planck Operator with Electromagnetic Fields (Communications in Mathematical Research, 2021)
We consider a Fokker-Planck operator with electric potential andelectromagnetic fields. We establish the sharp weighted and subelliptic estimates, involving the control of the derivatives of electric potential and electromagnetic fields. Our proof relies on a localization argument as well as a carefulcalculation on commutators.
Keywords: Maximal estimate; global hypoellipticity; Fokker-Planck operator.